Comparative Study of Intrathecal Bupivacaine with Dexmedetomidine versus Fentanyl in Lower Limb Orthopedic Surgeries - Aqeel Ahmad, Jatendar Wadhwani, Sibtain Raza, Neelam Noreen, Khan Muhammad Yaqub, Sadia Majeed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Spinal anesthesia is commonly used in lower limb orthopedic surgeries. Adding adjuvants to intrathecal bupivacaine enhances the quality and duration of anesthesia. Dexmedetomidine, a selective α2-adrenergic agonist, and fentanyl, a potent opioid, are both used as intrathecal adjuvants but differ in their efficacy and side effect profiles. Objective: To compare the onset, duration, analgesic quality, sedation levels, and adverse effects of intrathecal bupivacaine combined with either dexmedetomidine or fentanyl in patients undergoing lower limb orthopedic surgeries. Methods: This comparative clinical study included 70 patients undergoing elective lower limb orthopedic surgery at the University of Lahore Teaching Hospital and CMH Rawalpindi between June 2022 and June 2023. Patients were randomized into two groups: Group BD received 12.5 mg hyperbaric bupivacaine with 5 µg dexmedetomidine, and Group BF received 12.5 mg bupivacaine with 25 µg fentanyl. Onset and duration of sensory and motor block, duration of analgesia, sedation scores, and adverse effects were recorded and analyzed. Results: Group BD showed significantly faster onset of sensory and motor block, longer duration of block, and prolonged analgesia compared to Group BF (p < 0.001). Sedation was higher but within safe limits in Group BD. Pruritus and nausea were more frequent in the fentanyl group. Both groups remained hemodynamically stable without severe complications. Conclusion: Dexmedetomidine is a more effective and safer intrathecal adjuvant than fentanyl when combined with bupivacaine for lower limb orthopedic surgeries. It provides longer-lasting anesthesia and analgesia with fewer side effects. Keywords: Intrathecal anesthesia, Dexmedetomidine, Fentanyl, Bupivacaine, Orthopedic surgery, Spinal block, Analgesia.